Numerical Method for Fatigue Life Prediction of Liquid-Storage Tank via Crack Length and Depth - Jiafeng Lai; Ziyun You; Jiao Luo; Yuwei Wei; Xintian Liu (Advances in Materials Science and Engineering)
In the field of fatigue crack, crack size is a worthy topic to discuss. The relationship between crack length and depth is studied based on the Paris law, and a numerical model is established. The validity of the model is proved by comparing theoretical data with experimental data. In addition, the analysis of stress distribution of liquid-storage tank is carried out and the influence of hoop stress on the liquid-storage tank is considered. Remaining life of the tank is predicted through the numerical model. The feasibility of the numerical method is verified by predicting the remaining life of the tank, which provides a simple way for fatigue life prediction of the liquid-storage tank.